Role of regulatory bodies on energetic markets of European union - Mirko Klarić (Zbornik Radova Pravnog Fakulteta u Splitu, 2013)
This article analyses the role of regulatory body on energetic markets of European Union. In European Union it exist the single European market for natural gas and electricity. In the past, supplying with natural gas and electric energy was public service, and was a regal right of member states. Present, we have new regulation on that field, with divided authorities between European Union and Member States. In this article we shall analyze the role of the regulatory authorities on energetic markets of the European Union, with accent on the role of the most important energetic regulator, Agency for the Cooperation of Energy Regulators.